Metabolism of ethyl alcohol in rats exposed to cold environment. - Platonow, Nicolas. (University of Ottawa (Canada), 1967)
The study of the metabolism of ethyl alcohol in rats expoxsed to a cold environment was investigated by means of uniformly 14C-labeled ethyl alcohol. In rats exposed to cold for five days, the rate of metabolism of alcohol was accelerated, in contrast to their controls kept at room temperature. Moreover, the rate of absorption of alcohol from the site of its administration and the rate of its removal from the blood was greater in cold-exposed animals than in rats maintained at room temperature. The observed increase in the rate of metabolism of alcohol in cold-exposed rats, however, was not proportional to the rate of increase in the general metabolism. In cold-acclimated rats, whether or not pre-treated with alcohol, cold exposure resulted in an increased rate of alcohol metabolism. In cold-acclimated alcohol pre-treated rats, the increase in the rate of alcohol metabolism was proportional to the increase in overall metabolism. The data also indicate that the rate of alcohol metabolism is essentially independent when given in various doses. However, a dose dependence on the ratio of oxidation of alcohol to the total foodstuff utilization was demonstrated. No detectable changes in the alcohol oxidation rate were caused by partial hepatectomy. A single dose of an adrenergic blocking agent, phenoxybenzamine, immediately prior to the introduction of alcohol, produced a decrease in the oxidation rate of alcohol in rats exposed to cold. This reduction was more pronounced when cold-exposed rats were pre-treated with phenoxybenzamine from the onset of cold exposure, i.e. for five days prior to alcohol administration. The positive influence of the thyroid gland on the metabolic rate of alcohol in animals exposed to cold was demonstrated by blocking hormone production with potassium perchlorate during the cold conditioning period.
Keywords: Biology, Animal Physiology.